Microbleeds and clinical outcome in acute mild stroke patients treated with antiplatelet therapy: ADS post-hoc analysis. (July 2021) - Aoki, Junya; Iguchi, Yasuyuki; Urabe, Takao; Yamagami, Hiroshi; Todo, Kenichi; Fujimoto, Shigeru; Idomari, Koji; Kaneko, Nobuyuki; Iwanaga, Takeshi; Terasaki, Tadashi; Tanaka, Ryota; Yamamoto, Nobuaki; et al.
Highlights: This post-hoc research extracted the data from previous dual antiplatelet trial registry. The association of MBs with clinical outcome was evaluated. Whether patient characteristics depended on the number of MBs was also analyzed. MBs did not alter the rate of neurological deterioration and clinical outcome. Diastolic blood pressure and a history of ICH were universally related to the MBs. Abstract: Background and purpose: In this post-hoc analysis using acute dual study dataset, the impacts of cerebral microbleeds (MBs) after mild stroke on clinical outcome were investigated. Methods: The number of MBs on admission was categorized as 1) no MBs, 2) MBs 1–4, 3) MBs 5–9, and 4) MBs ≥ 10. The efficacy outcome was defined as neurological deterioration and stroke recurrence within 14 days. Safety outcomes included ICH and/or SAH as well as extracranial hemorrhages. Results: Of the 1102 patients, 780 (71%) had no MBs on admission, while 230 (21%) had MBs 1–4, 48 (4%) had MBs 5–9, and 44 (4%) had MBs ≥ 10. The number of MBs was not associated with the neurological deterioration and/or stroke recurrence (p = 0.934), ICH and/or SAH (p = 0.743), and extracranial hemorrhage (p = 0.205). Favorable outcome was seem in 84% in the No MBs group, 83% in the MBs 1–4, 94% in the MBs 5–9, and 85% in the MBs ≥ 10 (p = 0.304). Combined cilostazol and aspirin therapy did not alter any rates of efficacy and safety outcomes among the no MBs, MBs 1–4, MBs 5–9, and MBs ≥ 10 groups compared to aspirin alone (all p > 0.05). By multivariate regression analysis, a history of ICH and diastolic blood pressure were the independent parameters to all of the MBs criteria (presence, MBs ≥ 5, and MBs ≥ 10). Conclusions: MBs did not alter the clinical outcome at 3 months of onset. Elevated diastolic blood pressure and a history of ICH were the essential parameters related to the MBs.